Evaluation of Approximate Methodologies for Dimensioning Reinforced Concrete Columns According to NBR 6118 (International Journal of Geoscience, Engineering and Technology, 2025)
A comparative analysis was carried out between two semi-empirical methods for calculating double-supported columns established by ABNT NBR 6118 de 2023, “Concrete Structures Design – Procedure”, with emphasis on columns classified as moderately slender, with a slenderness index between 35 and 90. A comparison was made of steel consumption and the moment requesting calculation for 18 different columns (geometry and loading), considering the calculation methods (I) of the standard column with approximate curvature and, (II) of the standard column with approximate “κ” stiffness. The main differences obtained refer to the methodology for calculating second-order geometric effects for evaluating the structural deformability of bars after being requested by design loads. The analyzes carried out considered the three classifications of pillars provided for in the Brazilian Regulations: corner, end and center. Finally, it was concluded that methodology (II) standard column method with approximate “κ” stiffness proved to be more economical, with an indication of a reduction in the reinforcement rate of reinforced concrete columns varying in the order of 50% (± 34%) depending on the conditioning variables of each element analyzed.
Keywords: Reinforced Concrete Structures; Reinforced Concrete Columns; Buckling; Dimensioning; 2nd Order Effects